Major postoperative complications following elective resection for colorectal cancer decrease long‐term survival but not the time to recurrence. (February 2015) - Odermatt, M.; Miskovic, D.; Flashman, K.; Khan, J.; Senapati, A.; O'Leary, D.; Thompson, M.; Parvaiz, A.
Abstract Aim The aim of the study was to determine the effect of major complications after colorectal cancer surgery on survival and time to recurrence. Method Patients having a curative colorectal cancer resection and a follow‐up of at least 3 years were identified from a prospective database. Major complications were defined as Clavien–Dindo Grades 3b or 4 and their impact on time to recurrence and mortality was analysed by univariate and multivariable analysis. Postoperative death within 30 days or during the initial hospitalization (Clavien–Dindo Grade 5) was a priori excluded. Results From 2003 to 2012, 868 colorectal cancer resections resulting in 63 (7%) major postoperative complications including deaths (Clavien–Dindo ≥ 3b) were identified. After exclusion of Grade 5 complications (postoperative or in‐hospital deaths), 844 resections with 39 (5%) major complications remained for analysis. Median follow‐up time was 5.7 years. Using the Kaplan–Meier method, the estimated crude 5‐year overall survival probability was 78% (95% CI 75–81) in the group without and 65% (95% CI 51–83) in the group with major complications (P = 0.009, log‐rank test). Major complications were a significant negative predictor for overall survival (hazard ratio 2.42, 95% CI 1.41–4.14) when adjusted for sex, age, American Society of Anesthesiologists grade, tumour site (colon vs rectum), R stage and tumour stage. However, in both univariate and multivariable analysis, major complications were not a significant predictor for time to recurrence (hazard ratio 1.29, 95% CI 0.56–2.99). Conclusion Non‐lethal major postoperative complications seem to have a negative long‐term impact on survival but not on time to recurrence.